Desenvolvimento de protetor nasal anatômico para recém-nascidos em uso de pronga - Costa, Luana Cavalcante (2019)
The study object of this research was the development of na anatomic nasal protector for newborns using prongs, given the problem related to the high incidence of nasal injuries that can be avoided. In literature, effective and safe materials, as we as their forms and sizes, to avoid and/or mitigate such injuries are not clearly shown. Accordingly, it was aimed to enhance the desing of three sizes of nasal protectors based on anatomical measurements; to materialize the hydrocolloid protectors; to identify the effective method of sterilization; and to evaluate the microbiological safety and the stability of anatomical nasal protectors after appropriate sterilization. This is a descriptive study, with tecnological production, based on the Product Development Process, which covered the macrophase of development involving the phases of informational Project, conceptual Project and detailed Project, from March 2017 to February 2019. The enhancement of the nasal protector disigns was achieved by means of the measurements of the nose wing, width of the columella and áreas of the right and left nasal introitus, which resulted in three nasal protectors classified as: 1 – appropriate weight for gestational age; 2 – low weight for gestational age; and 3 – very low weight for gestational age. The materialization took palce through cutting in hydrocolloid plates, and then there was the reprocessing by five sterilization methods: ultraviolet and gamma radiation, gaseous formaldehyde, hudrogen peroxide plasma and saturated steam under pressure. The microbiological tests signalized Gram-positive bacterial growth for the formaldehyde and ultraviolet radiation methods, which also had Gram-negative bacteria in the latter case. Gamma radiation was effective against sterility of the material, maintenance of its macroscopic characteristics, absorption property in aqueous médium and physiological solution, as well as preservations of the constituents ofthe material. Therefore, we achieved the development of three nasal hydrocolloid protectors, with different and anatomical formats, reprocessed by gamma radiation, which preserved the material quality. After these tests, we noted safe and promising characteristics for the continuation o four studies, aiming the clinical evaluation in newborns using prongs.